The Graduate Students' E-Wallet Adoption Readiness and Behavioral Intentions - Bangguiyac, Glenn Ises (Journal of Interdisciplinary Perspectives, 2025)
In recent years, the increasing integration of digital financial services has prompted interest in understanding the factors that influence e-wallet adoption, especially among students in higher education. This study aimed to assess the readiness of graduate students for e-wallet adoption and behavioral intentions at a local university in the Philippines. Specifically, it examined respondents’ readiness along six key factors: perceived usefulness, perceived ease of use, social influence, facilitating conditions, perceived security, and perceived trust, and their relationship to behavioral intention toward online payments. A descriptive-correlational research design was employed, and a validated survey questionnaire was administered to a total of 195 respondents, selected from a population of 285 graduate students enrolled in the second semester of the 2024-2025 academic year. The data were analyzed using descriptive statistics, One-way ANOVA, and Pearson’s correlation coefficient, with statistical significance set at 0.05. Findings revealed that the respondents strongly agreed with most indicators of adoption readiness, particularly in terms of perceived ease of use and usefulness. The study also found a firm behavioral intention to use e-wallets, especially for university-related financial transactions. Among socio-demographic variables, only educational attainment showed a significant difference in perceived usefulness. Moreover, all six factors of adoption readiness were significantly and positively correlated with behavioral intention, with perceived usefulness, ease of use, and facilitating conditions emerging as the strongest predictors. The study concludes that higher education students are generally ready and willing to adopt e-wallets, influenced primarily by how helpful and easy these systems are to use, as well as the support available to facilitate their adoption. These results suggest that institutions and service providers should enhance their security measures, digital infrastructure, and awareness campaigns to improve adoption further and sustain usage. The findings also support the application of the UTAUT framework in local e-wallet adoption contexts.